Women's experiences of mistreatment during childbirth and their satisfaction with care: findings from a multicountry community-based study in four countries. (12th January 2021) - Maung, Thae Maung; Mon, Nwe Oo; Mehrtash, Hedieh; Bonsaffoh, Kwame Adu; Vogel, Joshua P; Aderoba, Adeniyi Kolade; Irinyenikan, Theresa Azonima; Balde, Mamadou Dioulde; Pattanittum, Porjai; Tuncalp, Özge; Bohren, Meghan A
Abstract : Introduction: Experiences of care and satisfaction are intrinsically linked, as user's experiences of care may directly impact satisfaction, or indirectly impact user's expectations and values. Both experiences of care and satisfaction are important to measure so that quality can be monitored and improved. Globally, women experience mistreatment during childbirth at facilities; however, there is limited evidence exploring the mistreatment and women's satisfaction with care during childbirth. Methods: This is a secondary analysis of a cross-sectional survey within the WHO study 'How women are treated during facility-based childbirth' exploring the mistreatment of women during childbirth in Ghana, Guinea, Myanmar and Nigeria. Women's experiences of mistreatment and satisfaction with care during childbirth was explored. Multivariable logistic regression modelling was conducted to evaluate the association between mistreatment, women's overall satisfaction with the care they received, and whether they would recommend the facility to others. Results: 2672 women were included in this analysis. Despite over one-third of women reporting experience of mistreatment (35.4%), overall satisfaction for services received and recommendation of the facility to others was high, 88.4% and 90%, respectively. Women who reported experiences of mistreatment were more likely to report lower satisfaction with care: women were more likely to be satisfied if they did not experience verbal abuse (adjusted OR (AOR) 4.52, 95% CI 3.50 to 5.85), or had short waiting times (AOR 5.12, 95% CI 3.94 to 6.65). Women who did not experience any physical or verbal abuse or discrimination were more likely to recommend the facility to others (AOR 3.89, 95% CI 2.98 to 5.06). Conclusion: Measuring both women's experiences and their satisfaction with care are critical to assess quality and provide actionable evidence for quality improvement. These measures can enable health systems to identify and respond to root causes contributing to measures of satisfaction.